Study of the Group Controlling on Large-Capacity DC Charging Piles for Peak Load Regulation - Zuping ZHANG; Qiyu CHEN; Xiuyuan YANG; Yuhuan HE (发电技术)
Under the development trend advocated by the new energy policy, the development of new energy vehicles in China has made great progress, and the battery energy density of electric vehicles has increased. The power of the DC charging pile charged by the corresponding electric vehicle power battery is getting higher and higher, so that the charging power of the DC charging pile accounts for an increasing proportion of the total load power of the distribution layer, which brings new challenges to the planning and construction of the distribution network. According to the arbitrarily interruptible charging process of the electric vehicle, it is proposed that when the total scale of the electric vehicle reaches a certain amount, the overall charging power of the electric vehicle can be flexibly controlled, thereby achieving the purpose of peak shaving for the power grid. Through the analysis of the power and control mode of the electric vehicle charging pile, it is concluded that when the number of DC charging piles and their total power in the distribution network load reaches a certain scale, in the cluster control mode, it is more suitable to participate in the peaking of the distribution network layer.